GC-MS Analysis of Bio-Active Compounds in Methanolic Extract of Punica Granatum L. Root - Ashwini, V. Naga; M, Revathi.; Pramila, R.; Manjunathan, J. (Journal of Neonatal Surgery, 2025)
There have been reports of phytochemical constituents from Punica granatum L.species. There are currently no reports on phytochemical constituents or biological activity of root extracts. The objective of this study was to identify the bioactive substances in methanol extract of root of Punica granatum L. Several phytochemical constitutions were found in the root part of Punica granatum L. The methanol extract of root of Punica granatum L. was exposed to a gas chromatography-mass spectrometry (GC-MS) analysis using GC-MS equipment. The methanolic extract of Punica granatum contains a variety of phytochemical compounds, according to the GC-MS analysis. 16 compounds in all, composition of the methanolic extract, were identified. It is clear from the data that root of Punica granatum is a plant of phytopharmaceutical significance and contains a variety of phytocomponents. Additional research is required to identify the active components of the extract and to clarify their precise mechanisms of action in different disorders.